7 - ‘I am an African’: A Critical Examination of the Politics of Transnational Identity within the Context of African Integration - Fagbayibo, Babatunde (Africa Development, 2021)
When an African asserts that ‘I am an African’, at what point can it be established that such a statement is directly influenced by his or her identification with integration initiatives at either the regional and/or continental levels? This article explores the identity-regional integration interface by situating the variables that inform or shape such a nexus. The article argues that such identity rests on certain structural contingencies, which are either inchoate or non-existent in the African context. The dearth of empirical data to capture the trend of transnational identification, limited civil society participation, and stunted development of regional integration process are diminishing factors. Ensuring the structural contingencies of transnational identification require more than the emotive appeal of pan-Africanism. It is in this context that this article offers the specific measures that can help enhance and strengthen the strategic nexus between regional integration and transnational identification in Africa.